2012
DOI: 10.1039/c2ay25512j
|View full text |Cite
|
Sign up to set email alerts
|

Electroanalytical properties of screen printed shallow recessed electrodes

Abstract: We report the fabrication of novel carbon based screen printed disc-shaped recessed electrodes (250 mm radius) which are electrochemically characterised and contrasted to other screen printed sensors previously reported upon within the literature. In these circumstances, the electrode is fabricated entirely through screen printing and the electrode geometry is defined by the dielectric (inert polymer) producing shallow recessed electrodes. In comparison to co-planar carbon screen printed electrodes, the shallo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…This electrochemical probe receives considerable attention owing to its very important role as a cofactor in many naturally occurring enzymatic reactions, and mainly because of the potential application in over 300 NAD + /NADH À dependent dehydrogenase-based biosensors [21][22][23][24][25][26][27] and consequently its electrochemical characteristics are hugely important. The kinetic parameter, 4 is tabulated as a function of peak-to-peak separation (DE P ) at a set temperature (298 K) for a one-step, one electron process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This electrochemical probe receives considerable attention owing to its very important role as a cofactor in many naturally occurring enzymatic reactions, and mainly because of the potential application in over 300 NAD + /NADH À dependent dehydrogenase-based biosensors [21][22][23][24][25][26][27] and consequently its electrochemical characteristics are hugely important. The kinetic parameter, 4 is tabulated as a function of peak-to-peak separation (DE P ) at a set temperature (298 K) for a one-step, one electron process.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Metters et al 6 have shown the constant diverse use of screen-printed sensors to many electrochemical targets, including chromium, 7 hydrazine 6 and atropine, 8 to name a few. Many researchers have expressed the need for miniaturisation of electrochemical setups and for the continuation of electroanalytical studies.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported on the design, fabrication and implementation of various screen‐printed electrode configurations exploring novel working electrode materials 6–9 and geometries 10–12. One such example includes the fabrication of platinum 7 and gold 6 screen‐printed sensors which were applied towards the electroanalytical sensing of chromium species (VI and III) in the case of the gold sensor, and both hydrazine and hydrogen peroxide for the case of the platinum sensor. Crucially, it was determined that the requirement for electrode potential cycling prior to utilisation (as is the case for bulk noble metal macro electrodes in order to form an oxide upon the electrode surface) was alleviated in the case of the screen‐printed sensors owing to the noble metal utilised within the screen‐printing process being in the form of an oxide.…”
Section: Introductionmentioning
confidence: 99%
“…This screen-printed electrode design has been previously reported. 26,28,29,33,[40][41][42][43][44] For the case of each fabricated electrode, rst a carbon ink formulation (Product Code: C2000802P2; Gwent Electronic Materials Ltd, UK), which is utilized for the efficient connection of all three electrodes and as the electrode material for both the…”
Section: Electrochemistrymentioning
confidence: 99%